Outcomes of Neonatal Candidiasis: The Impact of Delayed Initiation of Antifungal Therapy - Heather Cahan; Jaime G. Deville (International Journal of Pediatrics)
Objective/Methods. To determine the outcomes of invasive neonatal candidiasis before institution of routine antifungal prophylaxis, we conducted a retrospective review of cases of invasive candidiasis in newborns in a referral-based neonatal intensive care unit located in a single tertiary academic center between January 1998 and December 2002. Results. Sixty-three newborns with invasive neonatal candidiasis were identified. Overall mortality rate was 35%. Virtually every infant had a central venous catheter (CVC), required mechanical ventilation and previous administration of antibacterial agents. Delayed institution of antifungal therapy was associated with increased mortality. In addition, length of hospitalization, duration of prior antibacterial therapy, mechanical ventilation, and CVC use, as well as evidence of end-organ disease, were associated with an adverse outcome. Conclusions. Reliance on available laboratory tools in cases of invasive neonatal candidiasis can result in delayed diagnosis and increased mortality. A risk-factor-based approach to empirical treatment could be justified in this setting.